Lactobacillus Ameliorates SD-Induced Stress Responses and Gut Dysbiosis by Increasing the Absorption of Gut-Derived GABA in Rhesus Monkeys - Zhao, Ning; Shu, Yan; Jian, Chenxing; Zhou, Zili; Bao, Haijun; Li, Xianguo; Cheng, Xukai; Zhao, Ying; Jin, Si; Shu, Xiaogang (Frontiers in Immunology, 2022)
Sleep deprivation (SD) has become a health problem in the modern society. Although probiotics supplementation has been proved to improve SD-induced gut dysbiosis, the potential neuroendocrine mechanisms remain elusive. In this study, thirty rhesus monkeys (RMs) were recruited. Paradoxical sleep, bright light and noise were used to build RM SD model. We examined the plasma GABA, stress hormones and inflammatory cytokines using ELISA assays. 16S ribosomal DNA sequencing and untargeted metabolomics sequencing were employed to detect gut microbial community and metabolites, respectively. The results of our study showed that RMs subjected to SD had elevated plasma stress hormones (such as cortisol and norepinephrine) and proinflammatory cytokines (such as TNF-α, IL-6 and IL-8), and a decreased anti‐inflammatory cytokines IL-10 level. Additionally, SD could give rise to a significant change of gut microbiota and metabolites. The differential gut microbiota and metabolites caused by SD were enriched in the signaling pathways related to GABA metabolism. Pearson correlation analysis revealed that there is a significant correlation between plasma GABA and SD-induced stress responses and gut dysbiosis. The supplementation of GABA-producing probiotics could significantly increase the relative abundance of Lactobacillus and plasma GABA levels, and reverse SD‐induced stress responses and gut dysbiosis. Therefore, we speculated that SD-induced stress response and gut dysbiosis might be an outcome of reduced gut-derived GABA absorption. The supplementation of GABA-producing Lactobacillus might be beneficial for the treatment of SD-induced intestinal dysfunction.